A KONSEP PENDIDIKAN HOLISTIK DI PESANTREN: ANALISIS TERHADAP PEMIKIRAN IMAM AL-GHAZALI: KONSEP PENDIDIKAN HOLISTIK DI PESANTREN: ANALISIS TERHADAP PEMIKIRAN IMAM AL-GHAZALI - Tukiyah, Ricki Yakup; Betty Maulirosa Bustan (Pascasarjana Universitas Al-Qolam Malang, 2024)
Pesantren is the oldest Islamic educational institution in Indonesia which still has a big role in the success of Islamic education programs. However, it is unfortunate that not all pesantren are able to adapt to the times. So that it makes Islamic education tends to be left behind. But on the other hand, not a few pesantren have been able to adapt very well to the times, this is because the pesantren has implemented holistic education in its curriculum. This research is a qualitative research based on literature review. The purpose of this study is to find the concept of holistic education in Islamic boarding schools and its correlation with the thinking of Imam al-Ghazali. The results of this study found that the concept of Islamic holistic education in Islamic boarding schools is in line with the thinking of Imam al-Ghazali which aims to form a complete human being. Keywords: Education, Holistic, Islamic Boarding School, al-Ghazali